Non-Alcoholic Fatty Liver Disease in Obese Youth With Insulin Resistance and Type 2 Diabetes - Scapaticci, Serena; D’Adamo, Ebe; Mohn, Angelika; Chiarelli, Francesco; Giannini, Cosimo (Frontiers in Endocrinology, 2021)
Currently, Non-Alcoholic Fatty Liver Disease (NAFLD) is the prevalent form of chronic liver disease in children and adolescents worldwide, especially in Western nations. Simultaneously to the epidemic spreading of childhood obesity, the rate of affected young has dramatically increased in the last decades with an estimated prevalence of NAFLD of 3-10% in pediatric subjects in the world. The continuous improvement in NAFLD knowledge has significantly defined several risk factors associated to the natural history of this complex liver alteration. Among them, Insulin Resistance (IR) is certainly one of the main features. As well, not surprisingly, abnormal glucose tolerance (prediabetes and diabetes) is highly prevalent among children/adolescents with biopsy-proven NAFLD. In addition, other factors such as genetic, ethnicity, gender, age, puberty and lifestyle might affect the development and progression of hepatic alterations. However, available data are still lacking to firmly confirm whether IR is a risk factor or a consequence of hepatic steatosis. There is also evidence that NAFLD is the hepatic manifestation of Metabolic Syndrome (MetS). In fact, NAFLD often coexist with central obesity, impaired glucose tolerance, dyslipidemia, and hypertension, which represent the main features of MetS. In this Review, main aspects of the natural history and risk factors of the disease are summarized in children and adolescents. In addition, the most relevant scientific evidence about the association between NAFLD and metabolic dysregulation, focusing on clinical, pathogenetic and histological implication will be provided with some focuses on the main treatment options.